Comparative evaluation of population effect and economic potential of biological suppression tactics versus chemical control for squash bug (Heteroptera: Coreidae) management on pumpkins - Olson, D. L.; Nechols, James R.; Schurle, Bryan W. (My University, 1996)
Field releases of the indigenous egg parasitoid Grayon pennsylvanicum (Ashmead) resulted in a 4-fold reduction in squash bug, Anasa tristis (De Geer), densities on 'Jack-O-Lantern' pumpkins in 1991. However, pest populations subjected to parasitoids were consistently higher, and fruit yields and quality lower, than on plants that were treated with the insecticide, esfenvalerate, When the squash bug-resistant 'Green-Striped Cushaw' was used, the difference in pest densities on parasitoid-released and insecticide-treated plants was only half of that observed on the susceptible cultivar. In 1992, under abnormally wet, cool conditions, squash bug densities were higher on insecticide-treated plants and lower on plants where parasitoids were released than in 1991. Fruit quality for both cultivars was substantially reduced in all treatments in 1992, The wet, cool conditions apparently had less of an effect on pest densities and fruit yields on resistant pumpkins than on susceptible pumpkins. The expected net income for insecticide-treated pumpkins was substantially lower in 1992 than in 1991. Where biological control and host plant resistance were combined, loss in expected net income in 1992 was considerably less than in 1991. Although costs associated with biological control were very high relative to the revenues, integrating biological control with host plant resistance may have some potential as an alternative management strategy.
Citation: Olson, D. L., J. R. Nechols, and B. W. Schuhle. (1996). Comparative Evaluation of Population Effect and Economic Potential of Biological Suppression Tactics Versus Chemical Control for Squash Bug (Heteroptera: Coreidae) Management on Pumpkins. Journal of Economic Entomology 89 (3): 631–39. https://doi.org/10.1093/jee/89.3.631.
Keywords: Gryan pennsylvanicum; Biological control; Economic analysis; Squash bug